The War Concept in Chinese Linguistic Culture - Oleg I. Kalinin; Alexander V. Ignatenko (RUDN Journal of Language Studies, Semiotics and Semantics)
The general values and beliefs of society can be reflected through the attitude towards war. This work is devoted to the identification and analysis of linguistic and cultural concepts of war and their nature in the Chinese linguistic consciousness. Against the background of the foreign policy rapprochement between Russia and China, which stimulates mutual cultural and educational exchange and contacts in various fields, it seems important to consider the conceptual and axiological content of the concept frame WAR (战争) and its interpretation in Chinese linguoculture. In this regard, the purpose of this study is to consider the conceptual concepts of the socio-political phenomenon of war of Chinese cultural speakers in their linguistic consciousness. To achieve this goal, research tasks were consistently solved: the cultural and historical experience of understanding the phenomenon of war in the Chinese cultural tradition, in particular in Chinese philosophy and literature, was determined; the results of a definitional etymological analysis of lexemes representing the concept of WAR were presented; the results of previous studies of phraseological units with cultural and semantic components of the concept of WAR are summarized; the features of the representation of various military conflicts in the modern media discourse of the China are considered; the results of previously conducted associative experiments with the stimulus word “war” for representatives of Russian and Chinese linguistic cultures are interpreted; the data obtained are compared with the results of a study of intercultural variability in the perception of metaphorical models with the sphere of the goal is WAR. The analysis of attitudes towards war in the context of cultural parameters represented in the linguistic structures and speech practices of the people allows for a better understanding of the basic principles and values on which the mentality of various national cultures is based. In this regard, it seems relevant not only to identify the components of the WAR concept frame, but also, in particular, to study its various linguistic representations at various linguistic levels.